Exploring personality traits in EFL students’ speaking skills through Project-Based Learning - Lucyana Astrid Tri Susanti; Ulfatul Ma’rifah; Tri Yuli Ardiyansah (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
Recent studies have increasingly emphasized the importance of personality traits in shaping English as a Foreign Language (EFL) learners’ speaking performance, particularly in communicative classroom practices. However, in classroom practice, students demonstrate different levels of speaking participation. In addition, the use of less communicative teaching methods continues to limit students’ opportunities to practice speaking in  interactive contexts. Despite growing attention to personality in language learning, limited research has explored how these differences affect speaking participation in EFL settings, particularly within Project-Based Learning (PjBL) contexts at the secondary school level. Therefore, this study aims to address this gap by investigating personality differences in speaking participation. This study employed a qualitative approach with a case study design. The participants were 15 eleventh-grade students at one of state Islamic senior high school in Gresik. Data were collected using the Eysenck Personality Questionnaire–Revised (EPQ-R) to classify students’ personality types (introvert, ambivert, and extrovert) and a speaking performance questionnaire to analyze students’ speaking behavior during PjBL implementation. Additionally, data were obtained through classroom observations, semi-structured interviews, and documentation. The data were analyzed using thematic analysis following the stages proposed by Virginia Braun and Victoria Clarke. The findings indicate that extroverted students tend to be more active, confident, and spontaneous in speaking, particularly during group discussions and project presentations. Ambiverted students demonstrate flexible participation depending on task demands. In contrast, introverted students show more structured and cautious participation and require longer preparation time before speaking. The implementation of Project-Based Learning effectively facilitates students’ speaking skills across different personality types through collaborative and communicative activities. Therefore, Project-Based Learning can be considered an inclusive teaching approach to enhance EFL students’ speaking skills.